2011
DOI: 10.1097/bsd.0b013e3181bfdd07
|View full text |Cite
|
Sign up to set email alerts
|

Lumbar Microdiscectomy Versus Sequesterectomy/Free Fragmentectomy

Abstract: We argue that microscopic sequestrectomy is more successful with lesser operating time, fewer intraoperative complications, and lesser reherniation rate compared with conventional microdiscectomy in which patients are selected according to well-defined criteria, which is largely dependent on the competence of the annulus/posterior longitudinal ligament.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
24
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 0 publications
4
24
0
Order By: Relevance
“…Visualization of and instrument accessibility to the intervertebral disc space are limited. Furthermore, there is the possibility of the failed back syndrome related to diminished disc height1,6,7,14,15,17). Thus, we attempted to remove the normal disc materials as little as possible and eventually performed only fragmentectomy.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Visualization of and instrument accessibility to the intervertebral disc space are limited. Furthermore, there is the possibility of the failed back syndrome related to diminished disc height1,6,7,14,15,17). Thus, we attempted to remove the normal disc materials as little as possible and eventually performed only fragmentectomy.…”
Section: Discussionmentioning
confidence: 99%
“…They also reported that patients with stable fibrous rings and small defects (3 mm or less) had a good success rate. Fakouri et al6) reported successful sequestrectomy in patients who met their inclusion criteria : the free disc fragment was localized posterior to the PLL and the annular tear was up to 5 mm without significant bulging of the disc. This decision was made intraoperatively by assessing the integrity of the annulus fibrosus and the PLL, but the determinations were very subjective and dependent on each surgeon's experience.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations